Comparative Analysis of Power in the Urban Communities of Different States: Delbert Miller’s Project - Valery Georgievich Ledyaev (Сравнительная политика)
The article deals with the first analyses of power in urban communities in different countries conducted by Delbert Miller. The author examines the special features, stages, methodology and main conclusions of the project. Analyzing at the same time the limitations of the Miller’s work, the author, however, admits a powerful influence of its results on the following empirical projects.